Analysis of Patient Satisfaction with the Quality of Health Services at the Baros Health Center, Sukabumi City - Siti Rismawati Dewi; Johan Budhiana; Enung Tati Amalia (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: The development of science and technology has made people more selective in choosing quality health facilities to get the best service and achieve high satisfaction. Objectives: The study aimed to analyze patient satisfaction with the quality of health services at the Baros Health Center, Sukabumi City—methods: This type of descriptive research. The population is patients who visit the Baros Health Center with a sample of 248 people. The sampling technique is proportional random sampling and accidental sampling. Methods of data collection using a questionnaire. Methods of data analysis using IPA, KANO, and IPA-KANO Integrity. Results: The results showed that health services are considered very important (4.67), the performance of health services is very good (4.22), and there is still a gap (-0.45). Priority indicators that must be improved are in the aspect of the ability of health workers to prioritize immediate action, the ability of health workers to prioritize immediate action, while the good priority indicators are the aspects of indicators that are already good the aspects of cleanliness and comfort of the examination room. examination room, the CSI value is 0.78, which is in the satisfied category. Conclusions: It is hoped that the Baros Health Center will conduct periodic satisfaction surveys to evaluate a service provided to create quality services so that patient satisfaction will be higher.